Discrete Spectrum of 2 + 1-Dimensional Nonlinear Schrödinger Equation and Dynamics of Lumps - Javier Villarroel; Julia Prada; Pilar G. Estévez (Advances in Mathematical Physics)
We consider a natural integrable generalization of nonlinear Schrödinger equation to 2+1 dimensions. By studying the associated spectral operator we discover a rich discrete spectrum associated with regular rationally decaying solutions, the lumps, which display interesting nontrivial dynamics and scattering. Particular interest is placed in the dynamical evolution of the associated pulses. For all cases under study we find that the relevant dynamics corresponds to a central configuration of a certain N-body problem.